Sex in the city: Uncovering sex-specific management of equine resources from prehistoric times to the Modern Period in France. (February 2022) - Clavel, Benoît; Lepetz, Sébastien; Chauvey, Lorelei; Schiavinato, Stéphanie; Tonasso-Calvière, Laure; Liu, Xuexue; Fages, Antoine; Khan, Naveed; Seguin-Orlando, Andaine; Der Sarkissian, Clio; Clavel, Pierre; Estrada, Oscar; et al.
Highlights: Magdalenian horse hunt not focused on isolated bachelors. Iron Age and gallo-Roman sacrificial rituals have been preferentially oriented to male horses. During Antiquity, the Middle Ages and the Modern Period, cities are largely dominated by horse males. In rural contexts, females and subadults of both sexes were maintained to sustain production demands. Abstract: Sex identification from fragmentary archeozoological assemblages is particularly challenging in the Equid family, including for horses, donkeys and their hybrids. This limitation has precluded in-depth investigations of sex-ratio variation in various temporal, geographic and social contexts. Recently, shallow DNA sequencing has offered an economical solution to equine sex determination, even in environments where DNA preservation conditions is not optimal. In this study, we applied state-of-the-art methods in ancient DNA-based equine sex determination to 897 osseous remains in order to assess whether equal proportions of males and females could be found in a range of archeological contexts in France. We found Magdalenian horse hunt not focused on isolated bachelors, and Upper Paleolithic habitats and natural traps equally balancing sex ratios. In contrast, Iron Age sacrificial rituals appeared to have been preferentially oriented to male horses and this practice extended into the Roman Period. During Antiquity, the Middle Ages and the Modern Period, cities emerged as environments largely dominated by horse males. This strong sex-bias was considerably reduced, and sometimes even absent, in various rural contexts. Combined with previous archaeozoological work and textual evidence, our results portray an urban economy fueled by adult, often old, males, and rural environments where females and subadults of both sexes were maintained to sustain production demands.